Analisis Sistem Informasi Akuntansi Penjualan Kredit Di PT. Nusa Andhalan - Mohammad Fauzen Adiman; Syamhadi Syamhadi (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2023)
Every business is founded with the aim of making a profit for the owner in the future. Various strategies must be implemented, evaluated, modified, and developed continuously so that the company can maintain its existence. Not only in product marketing, but also aspects of human resources, information systems and management which are supported by the implementation of an internal control system must be the main concern of every business owner. In order to expand market share and sales volume, the Nuansa Karya Banyuwangi Store does not only serve cash sales, but also sells on credit. So that sales transactions increase. It's just that, the obstacle that is still being faced today is the continued increase in the number of uncollectible accounts every year. If this is not handled properly, it will cause losses for the company. So it is necessary to support data management based on Accounting Information Systems, which can support owners in making decisions. This qualitative descriptive study aims to determine the application of SIA at Nuansa Karya Store and its effectiveness in controlling receivables. The data were extracted from primary and secondary data sources. Both through the method of observation, interviews, and document analysis. Any data collected by researchers will be tested for validity through the triangulation method and extension of observations. The data were analyzed through three stages, namely: data presentation, data reduction, and drawing conclusions. From the results of field findings and discussions, it was concluded that Nuansa Karya's shop has not maximized the application of the Accounting Information System in managing sales transactions on credit. Receivables transaction data is recorded manually on the accounts receivable ledger and transaction evidence is not properly archived. In addition, there are dual duties of employees in carrying out the credit sales function. So that this condition does not optimally support the effectiveness of accounts receivable control and sales decision making.